(untitled) (Journal of Computational Mathematics, 1999)
A mixed finite element method is developed to approximate the solution of a strongly nonlinear second-order parabolic problem. The existence and uniqueness of the approximation are demonstrated and L^2-error estimates are established for both the scalar function and the flux. Results are given for the continuous-time case. 00a0